Conference calls and information spillover: the role of analyst participation - Awyong, Amanda; Cho, Young Jun; Yang, Holly (Review of Accounting Studies, 2026)
We examine the role of conference calls in creating information spillover within firms. We find that analyst participation in conference calls is positively associated with subsequent revisions in management forecasts, consistent with analysts’ questions prompting managers to collect additional information. We find that this effect strengthens when analysts pose more questions on new topics and when they ask questions with abnormally positive or negative tones. We also find that analyst participation has greater effects when analysts have more experience and higher forecasting ability. Further analyses demonstrate that analyst participation is associated with higher accuracy in subsequently revised forecasts. Overall, our results illuminate how conference calls contribute to firms’ internal information environment.